The limits of private ordering within modern financial markets - Awrey, A (Boston University, 2014)
From standardized contracts for loans, repurchase agreements, and derivatives, to stock exchanges and alternative trading platforms, to benchmark interest and foreign exchange rates, private market structures play a number of important roles within modern financial markets. These market structures hold out a number of significant benefits. Specifically, by harnessing the powerful incentives of market participants, these market structures can help lower information, agency, coordination, and other transaction costs; enhance the process of price discovery, and promote greater market liquidity. Simultaneously, however, successful market structures are the source of significant and often overlooked market distortions. These distortions – or limits of private ordering – stem from positive network externalities, path dependency, and power imbalances between market participants at the core of these market structures and those at the periphery. Somewhat paradoxically, these limits can erect substantial barriers to entry, insulate incumbents from vigorous competition, and undermine the emergence of new and potentially more desirable substitutes: thus entrenching less efficient market structures. Using the London Interbank Offered Rate (Libor) and the International Swaps and Derivatives Association determination committee (DC) mechanism as case studies, this paper seeks to better understand the limits of private ordering. It also explores how relatively modest changes to the public regulatory regimes governing these market structures could, in some cases, yield significant improvements.